Adaptation Strategies of the Colombian Hotel Industry During the Pandemic - López Cadavid, Diego Alejandro; Restrepo Morales, Jorge Aníbal; Vanegas López, Juan Gabriel; Arango Mesa, Maria Alexandra (Apuntes del CENES, 2024)
Different aspects related to business dynamics motivate the design and execution of strategies. In the case of the Colombian hospitality industry, the recent price regulation, the emergence of disruptive technologies, and events affecting public health demonstrate the need to outline appropriate tactics that lead to an adequate contextualized implementation. This study proposes an Analytic Hierarchy Process (AHP) model to evaluate the set of tactics and strategies most applicable to these current situation alternatives faced by hoteliers in the city of Medellin. The results of the evaluation indicate that intensive, generic business and defensive strategies are the most preferred. In addition, as expected, the results suggest that the pandemic has the greatest weight and should therefore be selected by hotel companies as the priority alternative on which to focus their strategies. Diferentes aspectos asociados a la dinámica empresarial motivan el diseño y ejecución de estrategias. En el caso de la industria hotelera colombiana, la reciente regulación de precios, el surgimiento de tecnologías disruptivas, así como los eventos que afectan la salud pública demuestran la necesidad de delinear tácticas apropiadas que lleven a una adecuada implementación contextualizada. Este estudio propone un modelo de análisis jerárquico de procesos (AHP) para evaluar el conjunto de tácticas y estrategias más aplicables a estas alternativas de situación actual que deben afrontar los hoteleros de la ciudad de Medellín. Los resultados de la evaluación indican que las estrategias intensivas, genéricas de negocio y defensivas son las preferidas. Adicionalmente, los hallazgos sugieren, como era de esperarse, que la pandemia tuvo el mayor peso y por lo tanto debe ser seleccionada por las empresas hoteleras como la alternativa prioritaria en la cual enfocar sus estrategias.